ANALISIS ATRIBUT PRODUK OLEH-OLEH SURAKARTA YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN - Ika Anjarsari; Anita Oktaviana Trisna Devi; Bekti Nugrahadi; Yunita Primasanti (ITB AAS Indonesia Surakarta, 2025)
This study to determin what product atributes and analysis of Surakarta souvenirs influence consumer purchasing decisions. This research method uses a quantitative approach. The sampling technique used is purposive sampling with a sample size of 400 respondents. The data collection technique in this study is to use primary data by distributing questionnaires in hardfile form. The data proscessing method used in this study uses descriptive analysis and correlation analysis with the help of IBM SPSS Statistic 25. The results of the study indicate that the location of purchase, packaging and uniqueness of the product are the three attributes with the highest valuse. In addition, this study found a significant positive correlation between gender and age with uniqe packaging.